Overuse syndromes of the shoulder - Pieper, H.-G. (1997)
Sports-specific strain on the shoulder joint, mostly unilateral, can lead to adaptive reactions if they occur during growth. Both male and female high-ranking athletes have become younger and younger in recent years. In addition to well-known stress reactions, biopositive adaptation processes can be found, not only in soft tissue but also in the skeleton. Unilateral hypertrophy of the humerus in the throwing arm of basketball players and unilateral thickening of humeral corticalis in the stroke arm of tennis players have been described in the literature. Our own investigations in handball players have shown changes of humeral retrotorsion of the throwing arm, leading to an increase in external rotation with a decrease of internal rotation. Athletes engaged in overhead sports with recurrent forceful motion in abduction/external rotation of the arm often complain of chronic shoulder pain without any history of trauma. In these patients, instability of the shoulder joint can usually be found, with a lesion of the glenoid labrum and/or an anterior labroligamentous periosteal sleeve and avulsion lesion. In most cases, the athlete is not conscious of the instability, which may lead to secondary functional impingement of the rotator cuff in the subacromial outlet. Surgery is indicated for patients who cannot be cured by conservative treatment such as muscular stabilisation: anterior reconstruction of the capsule and/or the glenoid labrum, and subacromial decompression and repair of the rotator cuff if necessary. Surgical treatment is successful in about 90% of the athletes.